PENGARUH KOMPENSASI TERHADAP MOTIVASI KERJA GURU TIDAK TETAP (GTT) DI KECAMATAN MELIAU KABUPATEN SANGGAU - Jumardi Budiman (STIE 'INDONESIA' Pontianak, 2016)
Compensation and motivational aspects are inseparable in human resource management. Compensation and motivation discount linkages and relationships that influence each other in supporting a person's performance. This study seeks to assess the degree of influence between variable compensation on work motivation on temporary teachers in the District Meliau Sanggau. The main problem of this study is: